2021
DOI: 10.9734/ajacr/2021/v9i430224
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Biological Activities of Eugenia caryophyllata Thunb Essential Oil

Abstract: Aims: In this study the antibacterial and antioxidant activities of the essential oil of Eugenia caryophyllata were investigated. Study design: The study contains determination of the chemical composition of the essential oil of E. caryophyllata and the in vitro evaluation of the antibacterial and antioxidant activity of this oil. Place and Duration of Study: The study was carried out at the laboratory of research on local animal products of Ibn-Khaldoun University, Tiaret, Algeria during the perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
1
0
2
Order By: Relevance
“…In a study done by Abdellah et al [27] they reported that Daucus carota honey has an antifungal effect against Candida albicans.…”
Section: Antifungal Activity Of Natural Honeymentioning
confidence: 99%
“…In a study done by Abdellah et al [27] they reported that Daucus carota honey has an antifungal effect against Candida albicans.…”
Section: Antifungal Activity Of Natural Honeymentioning
confidence: 99%
“…As folhas do E. globulus são uma das fontes naturais mais utilizadas na saúde (Monteiro et al, 2020). Ela possui altas concentrações em 1,8-cineol e alfa-pineno (Abdellah et al, 2021). Seus compostos previnem o desenvolvimento de fungos como Candida albicans, assim reduzindo sua virulência (Sukhikh et al, 2022).…”
Section: Consideram-se Ounclassified
“…Ces études ont porté sur des sujets variés tels que les variations morphologiques des populations (Klimko et al, 2007 ;Hafsi et al, 2017) ou l'activité des composés phénoliques présents dans l'écorce des racines (Chaouche et al, 2015). Elles sont cependant principalement axées sur l'obtention, la composition et l'activité, d'une part, de l'huile de cade obtenue par distillation du bois, cette huile étant très utilisée en médecine vétérinaire, en dermatologie et en médecine traditionnelle (Quézel et Gast, 1998 ;Loizzo et al, 2007 ;Julin, 2008 ;Abdellah et al, 2018 ;Al-Snafi, 2018), et, d'autre part, des huiles essentielles issues des feuilles, des baies, des cônes ou des écorces (Marongiu et al, 2003 ;Dob et al, 2006 ;Medini et al, 2013 ;Hayta et Bagci, 2014 ;Al-Snafi, 2018).…”
Section: Introductionunclassified